Comparison of Physicochemical and Functional Traits of Hanwoo Steer Beef by the Quality Grade - Lim, Dong-Gyun (Korean J Food Sci Anim Resour, 2014)
The physicochemical and functional traits for loin muscles of Hanwoo steers were compared by quality grade (QG). A total of 500 Hanwoo steers were slaughtered, their carcasses were categorized into four groups (QG 1++, 1+, 1, and 2), and the longissimus dorsi muscles were analyzed. QG 1++ group had the highest fat and lowest moisture content (p<0.05). QG 1++ showed higher L* and b* color values, higher cooking loss, and lower shear force values, compared with the other groups (p<0.05). The flavor, tenderness, juiciness, and preference scores by sensory evaluation were highly ranked for premium QG groups (1++ and 1+). Regarding the micro compounds, QG 1 and QG 2 had greater amounts of inosine monophosphate, and QG 2 had greater amounts of anserine, carnosine, and creatine, than QG 1++ (p<0.05). QG 1++ and 1+ had higher percentages of oleic acid (C18:1) than QG 2 (p<0.05). Within premium QG 1++ and 1+, the results of the nucleotides, free amino acids, dipeptides, and fatty acids did not show any distinctive differences. Hanwoo beef as determined by the current grading system was not significantly different in terms of functional components; the only significant difference was in intramuscular fat content.